Desain Bangunan Greenhouse untuk Pekarangan Pangan Berkelanjutan: Komunikasi Pemberdayaan Ramah Lingkungan untuk Ketahanan Pangan - Zubizaretta, Zaid Dzulkarnain; Setiyaningsih, Lian Agustina; Luthfi, Ahmad; Zainul’ID, Ahmad Bagus; Widayati, Sri (Institut Teknologi Adhi Tama Surabaya, 2024)
The service in this paper discusses the design and implementation of greenhouses for sustainable agricultural land, with a focus on environmentally friendly solutions to improve food security through effective empowerment communication. This activity involves a group of housewives in green living housing in the middle of the city. The Pekarangan Pangan Lestari (P2L) Group is located in Kelurahan Gadang, Malang City, East Java. This service refers to the challenges of food security in urban areas with a sustainable yard farming approach. The implementation method is observation, area measurement, adjustment of needs and design creation. Greenhouse design adapted to sustainable agricultural yard land. This offers a practical and measurable method for producing high-quality food in an urban environment. The design and structure of the greenhouse designed aims to optimize plant growth, save resources such as water and energy, and reduce the adverse effects of unpredictable weather patterns. The implementation of the greenhouse design has been adjusted to the needs of P2L and the conditions of the yard area by considering the economic side and environmentally friendly technology.